PENERAPAN METODE NAIVE BAYES UNTUK PREDIKSI STOK BARANG BANGUNAN DI TOKO BANGUNAN REJO MULYO - Munthohar, Ahmad Derry ali; Pribadi, Teguh; Sulistiawan, Agus (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2024)
In this era of a company, inventory is an important factor because a company's inventory will continuously be acquired, changed, and resold Tb. Rejo Mulyo is a company engaged in the business of buying and selling building materials. Which materials and building goods sold consist of various types of goods at different prices. Therefore it is important to plan stock inventory so that there is no stock buildup or delay. Based on the problems above, we need a stock prediction system that is in accordance with demand. Based on these problems, the researchers designed a web-based inventory system using the Naïve Bayes method. The Naïve Bayes method itself is an effective method for predicting inventory based on existing past data. so that it can produce predictive indicators correctly. After processing the prediction accuracy data using the confusion matrix, it produces an accuracy value of 61%, precision of 66% and recall of 50%, which means that the prediction is said to be successful. With this the naïve Bayes method can help us in predicting the determination of the stock of building goods in Tb. Rejo Mulyo